Produção de lipase por amostras de cunninghamella echinulata (UCP 1308) em meios contendo resíduos agroindustriais. - Sales, Paloma Santa Cruz de (2018)
Lipases (EC 3.1.1.3) are one of the groups of enzymes that have an immense variety of biotechnological applications and can be produced by bacteria, yeasts and filamentous fungi. The use of isolated samples of the caatinga soil is justified due to high biodiversity and biotechnological potential in the production of enzymes, besides the use of agroindustrial residues as substrates in minimizing production costs. In this work, the biotechnological potential of Cunninghamella echinulata samples isolated from the Caatinga of Pernambuco denominated UCP 060, UCP 1299 and UCP 1308 were evaluated for lipase production through a screening of fungi, selection of media using agroindustrial residues (post-fry oil and Effluent waste sorbet) and submerged fermentation with a complete factorial design 23 incubated at 37 ° C, 150 rpm, 168h. The results showed that the UCP 1308 sample presented the highest production of lipase with 26.4 U / mL at 96 h in medium 4, showing that the ice cream residue served as an excellent substrate for enzyme production. In this work it was proven that the elaboration of alternative means are economically viable for lipase production, providing the development of technologies in line with the principles of sustainability